Penggunaan Streptomyces sp. Sebagai Biokontrol Penyakit Layu Pada Tanaman Cabai Merah (Capsicum annuum L.) yang Disebabkan Oleh Fusarium oxysporum f.sp. capsici - ANINDA OKTAVIA RAHARINI; RETNO KAWURI; KHAMDAN KHALIMI (Agrotrop : Journal on Agriculture Science, 2012)
A research has been conducted to find out Streptomyces bacteria at Bukit Jimbaran, to inhibitionpotency of Streptomyces sp. to pathogenic fungi Fusarium oxysporum f.sp. capsici, and to find outantifungal activity of Streptomyces filtrate to F.oxysporum f.sp. capsici in chili (Capsicum annuumL.) plants. Streptomyces sp. isolation was done by platting method with selective media YMA (ISP4).Identification of Streptomyces sp. used Bergey’s book entitled Manual Determinative Bacteriology.Test inhibition against F.oxysporum f.sp. capsici and in vivo test used by dying the roots of the chili(C.annuum L.) plant with F.oxysporum f.sp. capsici and after 30 seconds the roots were dying withStreptomyces sp. culture, furthermore sterile soil on polybag watered by F.oxysporum f.sp. capsicispore and Streptomyces sp. culture at the same time. The result found five isolates Streptomyces sp.with different morphological. The antagonis test showed Streptomyces sp. 4 had ability (82%) againstFusarium, Streptomyces sp.1 (72%), Streptomyces sp.2 (64%), Streptomyces sp.3 (76%), andStreptomyces sp. 5 (32%). All Streptomyces suppressed the growth of Fusarium on chili plants inglass house (p<0,05). Streptomyces sp.4 suppressed Fusarium wilt disease in chili from 80% in controlto 8%.